Combating Illegal Immigration across Seas - Mustafa, Aws; Gazi, Mohammed (Journal of Legal Sciences, 2022)
The concern seemed clear due to the phenomenon of illegal immigration and flows that accompany it and reach the borders of countries in an unprecedented way, paid Countries to take the principle of cooperation as an optimal solution to overcome the challenges that accompanied illegal immigration. The challenges were to set rules to combat this phenomenon and put means to put an end to it , because it is clearly linked to crime through organized crime networks that facilitate the process of smuggling migrants through international waters. And to create roads that facilitate infiltration across the borders of the destination countries, taking advantage of the gaps existed in the contents of domestic and international laws. This increased the number of missing persons during smuggling operations, especially in international waters, due to the difficulty of crossing such borders and controlling the weather conditions that affect the smuggling process negatively. The smuggling networks use equipment not suitable for use in international waters.